Bile acids and incretins as modulators of obesity-associated atherosclerosis - Andrijana Kirsch; Juergen Gindlhuber; Diana Zabini; Elena Osto; Elena Osto (Frontiers in Cardiovascular Medicine)
Obesity is one of the major global health concerns of the 21st century, associated with many comorbidities such as type 2 diabetes mellitus (T2DM), metabolic dysfunction-associated steatotic liver disease, and early and aggressive atherosclerotic cardiovascular disease, which is the leading cause of death worldwide. Bile acids (BAs) and incretins are gut hormones involved in digestion and absorption of fatty acids, and insulin secretion, respectively. In recent years BAs and incretins are increasingly recognized as key signaling molecules, which target multiple tissues and organs, beyond the gastro-intestinal system. Moreover, incretin-based therapy has revolutionized the treatment of T2DM and obesity. This mini review highlights the current knowledge about dysregulations in BA homeostasis in obesity with a special focus on atherosclerosis as well as athero-modulating roles of incretins and currently available incretin-based therapies.